DAKWAH LITERASI DAN PERANANNYA DALAM MEMBANGUN MASYARAKAT BERPERADABAN DALAM Q.S. AL-‘ALAQ AYAT 4-5 - Junnifar, Ali; Darwati, Aan (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2022)
A survey showed that Indonesia have very low literacy level, which is ranked 62 out of 70 world countries, with 0.09 national ratio between reading materials and total population of Indonesia, which means one book was reserved in order for 90 persons per year. The underwhelming literacy culture in Indonesia was caused by the average citizens consideration of writing as a difficult, irritating and unimportant task. This leads to them interpreting writing activity as a routine task of doing copy-paste (copying existing works of literature), recording, and relying on memorization, even though humans tend to forgot many things everyday. The purpose of this research is to understand the definition of literature da'wah and its role in creating civilized societies, and to study the various mufasir opinions regarding the interpretation study of Q.S. al-'Alaq verses 4-5 which explains literature da'wah and the strategies in performing literature da'wah and find its role in creating civilized societies. The research type is library research in which it is a qualitative research type that tends to analize data inductively. This research type only observe and report adequately while prioritizing more on gathering data. This study delivers conclusion in form of literacy da'wah strategies and its role in creating civilized societies within perspective of Q.S. al-'Alaq verses 4-5 with five methods, in which the first one is to implement awareness on the importance of reading from childhood; the second, is to read and write as much as possible; the third, is to improve writing skills; the fourth, is to encourage creation of credible writing mediums; and the last method, is to encourage fair regulation of writing profession and credible media companies